The Influence of Project Based Learning (PjBL) Model on Creative and Entrepreneurship Learning Outcomes of Students of SMK Negeri 1 Palembang - Purnama, Putri; Lestari, Neta Dian; Pratiwi, Nova (Journal of Social Work and Science Education, 2023)
Project Based Learning (PjBL) is a learning model that creates a challenge by involving activeness, collaboration, between students in a project. This study aims to determine the effect of the PjBL Learning Model on Learning Outcomes of Creative Projects and Entrepreneurship Students of SMK Negeri 1 Palembang. The data collection technique uses observation of student activity and tests of learning outcomes for creative and entrepreneurial projects using the experimental method of the True Experimental Design type with the Posttest-Only Control Design form. Based on the results of the research and discussion, it can be concluded from testing the research using the Independent Sample T Test assisted by SPSS version 26 software with a significant level of 0.05, namely hypothesis 0.002, less than 0.05 (0.002 <0.05), it can be concluded that Ho rejected and Ha accepted, there is an influence of the PjBL Learning Model on Learning Outcomes of Creative Projects and Entrepreneurship Students of SMK Negeri 1 Palembang.